Analisis Perlindungan Hukum Terhadap Anak Di Bawah Umur Sebagai Saksi Korban Pelecehan Seksual di Polres Kabupaten Karo - Niken, Hanna; Saragih, Rayani (Universitas Medan Area, 2023)
The Juvenile Criminal Justice System is the entire process of resolving cases of children who conflict with the law, starting from the investigation to the guidance stage after a crime that conflicts with the law, children who are victims of criminal acts, and children who are victims of acts, confirming that children who conflict with the law, children who are witness to a crime. Children as witnesses to criminal acts provide information for investigation, prosecution, and examination in court regarding a criminal case that they heard, saw, and/or experienced. Children as witnesses tend to be easily influenced or even threatened with violence with various actions to change their testimony, for this reason, they need to be provided with legal assistance and protection. This research also aims to analyze the legal protection of minors as witnesses in criminal cases at the Karo Regency Police. This research is empirical juridical research with research sources using primary legal materials, secondary legal materials, and tertiary legal materials. Primary legal materials are the results of field research based on interviews, observations, and document studies at the Karo District Police, secondary legal materials in the form of Law Number 35 of 2014 concerning Child Protection and Law Number 11 of 2012 concerning Juvenile Criminal Justice System, literature study/ literature and other regulations relevant to this research.